Effect of cochlear implant in children suffering genetic hypoacusis caused by Waardenburg Syndrome and 35delG mutation - Sandra Elena Quintana Mirabal; Estela Morales Peralta; Alejandro Torres Fortuny; Antonio Paz Cordovés; Emilio Luis Morales Jiménez; Yesy Martín García; Gerda Alianna González Sánchez (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: Sensorineural hypoacusia is the most common form of hearing impairment, it is estimated that over 80% of all congenital hearing losses are from genetic origin, being distinguished in syndromic and non-syndromic; 35delG mutation is the most common cause of the first and Waardenburg syndrome (WS) is one of the most frequent in the last one; in both of them cases are usually identified patients with severe to profound hearing losses (HSP). The cochlear implant is considered an effective solution when the HSP do not get enough benefit through hearing aids. Objective: To analyze the results achieved with the use of cochlear implant in patients with HSP due to WS and 35delGmutation. Material and Methods: A descriptive cross-sectional study. Were studied patients with HSP of genetic cause, 27 due to 35delGmutation and 15 by WS. Hearing and logophoniatrics tests were performed. Results: Inner ear lesions happening in the in the studied patients it seems not affect the benefits of cochlear implant if general proper conditions are given. Conclusions: Cochlear Implant is a worthful therapeutic alternative for the hearing impaired due to these two studied illness; however, those with 35delG mutation, achieved best hearing performance categories.  Keywords: deafness, hearing loss, genetics, rehabilitation, hearing impairment correction.